Study on the excision and integration mediated by class 1 integron in Streptococcus pneumoniae. (October 2017) - Lin, Qun; Xu, Pusheng; Li, Jiaowu; Huang, Jinhua; Chen, Yin; Deng, Shuhuan
Abstract: As a novel antibiotic resistance mobile element, integron was recognized as a primary source of antibiotic genes among Gram-positive organisms for its excision and integration of exogenous genes. In this study, Streptococcus pneumoniae was subjected to investigate the excision and integration of class 1 integron with eight different plasmids. As the results indicated, excision in both att site and gene cassettes were successfully observed, which was further confirmed by integration assays and PCR amplification. The observation of class 1 integron mediated excision and integration of various exogenous antibiotics resistance genes may raise the attention of integrons as novel antibiotic resistance determinant in Gram-positive bacteria, especially in Streptococcus . Highlights: This is a study on class 1 integron in Gram-positive bacteria Streptococcus pneumoniae. The stronger excision efficiency was obtained when attC site on the left-hand neighbour comparing with attI. G/TTRRRY sequence was observed in the excised-cassettes integration consensus site.